Integrative multiomics evaluation reveals the importance of pseudouridine synthases in hepatocellular carcinoma - Jin, Zhipeng; Song, Mengying; Wang, Jianping; Zhu, Wenjing; Sun, Dongxu; Liu, Huayuan; Shi, Guangjun (Frontiers in Genetics, 2022)
Background. The pseudouridine synthases (PUSs) have been reported to be associated with cancers. However, their involvement in hepatocellular carcinoma (HCC) has not been well documented. Here, we assess the roles of PUSs in HCC. Methods. RNA sequencing data of TCGA-LIHC and LIRI-JP were downloaded from the Cancer Genome Atlas (TCGA) and the International Cancer Genome Consortium (ICGC), respectively. GSE36376 gene expression microarray was downloaded from the Gene Expression Omnibus (GEO). Proteomics data for an HBV-related HCC cohort was obtained from the CPTAC Data Portal. RT-qPCR assay was performed to analyse the relative mRNA expression of genes in clinical tissues and cell lines. Diagnostic efficiency was evaluated by ROC curve. Prognostic value was assessed using Kaplan-Meier curve, Cox regression model, and time-dependent ROC curve. Copy number variation (CNV) was analysed using GSCA database. Functional analysis was carried out with GSEA, GSVA, and clusterProfiler package. The tumor microenvironment (TME) related analysis was performed using ssGSEA, and ESTIMATE algorithm. Results. We identified 7 PUSs that were significantly upregulated in HCC and 5 of them (DKC1, PUS1, PUS7, PUSL1, and RPUSD3) were independent risk factors for patients’ OS. Meanwhile, the protein expression of DKC1, PUS1, and PUS7 was also upregulated and related to poor survival. Both mRNA and protein of these PUSs were highly diagnostic of HCC. Moreover, the CNV of PUS1, PUS7, PUS7L, and RPUSD2 was also associated with prognosis. Further functional analysis revealed that PUSs were mainly involved in pathways such as genetic information processing, substance metabolism, cell cycle, and immune response in HCC, and were closely associated with TME. Conclusion. PUSs may play crucial roles in HCC and could be used as potential biomarkers for the diagnosis and prognosis of patients.